Ampicillin Removal in Situ Oxidation Using a Double-layer-‎cathode Trickle Bed Electrochemical Reactor (TBER)‎ (Journal of University of Babylon for Engineering Sciences, 2024)
Ampicillin (AMP) is extensively used as an antibiotic in hospitals and veterinary clinics worldwide to combat bacterial infections. As a result, residues of this antibiotic are commonly identified in the wastewater released by these facilities. This study introduces an advanced oxidation process for efficiently removing ampicillin from wastewater using a double-layer-cathode trickle-bed electrochemical reactor (TBER). This system electro produces environmentally friendly hydrogen peroxide (H2O2) through oxygen reduction, which is then used to oxidize ampicillin in wastewater. The TBER features a high-porosity electrode (C-PTFE-SSM) with optimized operating parameters. The effectiveness of this electrochemical process was evaluated within a TBER measuring 120 mm wide, 110 mm high, and 40 mm deep. equipped with a stainless steel anode and a gas diffusion cathode made of carbon black polytetrafluoroethylene The evaluation focused on the removal of antibiotics, specifically ampicillin (AMP), using applied voltages ranging from 1 to 3 volts, electrolyte concentrations 0.5 M, electrolyte flow rates 25 to 250 mL/min, oxygen flow rates 2 to10 L/min, and ampicillin concentrations 100 ppm. The reaction temperature maintained constant at15°C and duration necessary for achieving maximum removal by electrochemical process within the TBER. The results indicate that the in-situ oxidation process conducted in the customized reactor holds significant potential for improving ampicillin elimination. Under optimal conditions, including a potential of 1 V, an Electrolyte concentration 0.5M H2SO4, electrolyte flow 200ml/min, oxygen flow 9L/min, ampicillin concentration 100ppm, reaction temperature 15°C, and a reaction time of 40 minutes, the highest achieved ampicillin removal rate was an impressive 93.6%. Under the ideal conditions.